What global fragmentation means for the WTO: Article XXIV, behind-the-border concessions, and a new case for WTO limits on investment incentives - Emily J. Blanchard (World Trade Organization (WTO), 2014)
The rapid rise in global fragmentation - foreign investment, global supply chains, and 'production sharing' - is fundamentally reshaping the multilateral trading system. This paper uses a simple economic modeling framework to understand how the global fragmentation phenomenon may reshape the WTO, and particularly its developing country members that are most affected by the rise in global production sharing and foreign direct investment. The paper argues that the surge in global production sharing, supply chain agreements, and investment has not only recast the role of existing GATT/WTO rules, but that these same forces also create a strong rationale for new multilateral disciplines pertaining to investment incentives and other 'behind-the-border' policies.
Keywords: F13; F15; F21; F23; 330; GATT WTO; International Investment; Global Supply Chains; Production Fragmentation; Multilateral Investment Agreements